Pengalaman Hidup Lulusan Sekolah Menengah Atas yang Menjalani Gap Year Dimasa Pandemi - Wicaksono, Eko Taris; Karyani, Usmi (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2023)
In 2020, when the COVID-19 pandemic occurred, it was recorded that only 38% of high school graduates continued their education in college, while in the following year, 2021, the field of coordination of improving the quality of teaching and religious moderation stated that only 50% of high school graduates continued their college education each year. This study explores the decision-making factors, experiences, and plans that high school graduates who undergo a gap year during the COVID-19 pandemic have—using a phenomenological qualitative method by giving an open-ended questionnaire to 69 high school graduate participants followed by interviews with 4 participants. This study reveals that the family's economic limitations are the most influencing factor, supported by an inner desire to become more independent and ease the burden on parents, not wanting to be idle and waste time, and interpreting the gap year as only delaying for specific reasons. They are gaining various positive experiences such as increasing life and economic independence, gaining work experience, and increasing social interaction skills, soft skills, and hard skills. Negative experiences such as unfair treatment in the world of work, oblique views, feelings of envy, disappointment, upset, upset, sadness, stress, and discouragement have an impact on psychosomatic disorders—plans to continue studying in the following year alongside work and business. Knowing the college major they want to pursue, there is a change of purpose in their intention to attend college. Special attention needs to be given to the school in assisting prospective high school graduates with the obstacles that may be faced in continuing their studies so that they can provide the best direction and solutions for students.